Applying second derivative synchronous fluorescence spectroscopy combined with Gaussian band fitting to trace variations of DOM fractions along an urban river. (February 2023) - Zhang, Xiulei; Nie, Lei; Gao, Hongjie; Yu, Huibin; Liu, Dongping
Highlights: SFS combined with Gaussian banding fitting acquired DOM for small-sample. 2D-COS was used to reveal the variations of DOM in town, urban, and rural region. PCMW2D were used to trace the variations of DOM along the whole river. Abstract: Synchronous fluorescence spectroscopy (SFS) combined with Gaussian band fitting, two-dimensional correlation (2D-COS) and perturbation-correlation moving-window two-dimensional (PCMW2D) can provide an excellent mothed to extract fluorescent components of dissolved organic matter (DOM) and reveal its variations in an urban river. Fifteen water samples were collected from the Anyanghe River, which flew across the town, urban, and rural regions. Five peaks (peak1 tyrosine-like, peak2 tyrosine-like, peak3 tryptophan-like, peak4 microbial humic-like, peak5 fulvic-like) were extracted using the Gaussian Amp model from the SFS in the river, while the peak1 only occurred in the rural region. The microbial humic-like in the town region accounting for 50.02 % was the representative substance. The tyrosine-like dominated in the rural regions, for its percentage range was 62.26 %-75.78 %. The average percnetage of tyrosine-like (29.77 %) in the urban region was similar to that of the tryptophan-like (21.86 %), microbial humic-like (25.56 %), and fulvic-like (22.82 %). Based on the two-dimensional correlation, the variation order of DOM fractions in the town and urban regions was tryptophan → tyrosine → microbial humic → fulvic, and the variation order in the rural region was tyrosine → tryptophan → microbial humic → fulvic. This indicated that the changing trend of DOM fractions existed from the labile protein-like to the stable humus in the whole river. According to the perturbation-correlation moving-window two-dimensional correlation spectroscopy, the spectral intensity of tyrosine-like should be linear increase in the town and urban regions, and concave increase in the rural region. The spectral intensity trend of tryptophan-like mainly was linear increase in the whole river. And the intensity of microbial humic-like showed the rough convex increase in the whole river. The trend of the fulvic-like in the town and rural regions was similar to the microbial humic-like. However the fulvic-like intensity in the urban region exhibited a trend from the concave increase to the convex increase, which was obviously different from the tyrosine-like, tryptophan-like and microbial humic-like. This attribute that the untreated domestic sewage in the urban region could discharge into the river. Therefore, for small amounts of samples, the SFS combined with Gaussian band fitting, 2D-COS and PCMW2D can be used as a powerful tool to investigate fluorescent components of DOM, and reveal their variations along the river.